Praktik Utang Piutang melalui Aplikasi Peer to Peer Lending Kredit Pintar dalam Perspektif Fatwa Dsn-MUI - Tutik Hidayati; Ramdan Wagianto; Hawa’ Hidayatul Hikmiyah (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2022)
Online loans are loans with a system through online media, one of which is the Smart Credit Application. Debt is one of the muamalah activities that is based on mutual cooperation between each other so that Muslims can do it if the debt and credit contracts are fulfilled properly. The focus of the problems in this study are: 1) The loan application process in the Smart Credit Application in Islamic law. 2) Debts that have not been paid off by the due date determined by the Smart Credit application in Islamic law. The type and approach of this research is library research with qualitative methods (library research). The collection technique used is the documentation technique, namely collecting various written sources including books, newspapers, and so on. Analysis of the data used in this study used descriptive qualitative. This study concludes that: 1) The loan process in the Smart Credit application based on the pillars and terms of the qardh contract has met the provisions of the DSN fatwa No: 19/DSN-MUI/IV/2001 concerning Al-Qardh. 2) Debt payments must be in accordance with the agreement, must not exceed the specified maturity limit, if it exceeds the maturity limit a fine will be imposed in accordance with the DSN DSN fatwa No: 17/DSN-MUI/IX/2000 concerning sanctions on capable customers who delay payment of debts.